Measuring housing affordability in São Paulo metropolitan region: Incorporating location. (February 2017) - Acolin, Arthur; Green, Richard K.
Abstract: This paper develops a novel measure of affordability for the São Paulo metropolitan region that combines housing costs and transportation costs, including opportunity cost associated with commuting time. The results for the 2007–2013 period indicate that the number of households spending > 30% of their income on housing or 45% or more on housing and transportation costs combined has been increasing rapidly. This measure of affordability that includes transportation costs provides a broader measure of housing needs to guide housing policy in addressing housing conditions that have negative effects on individual and social welfare. Highlights: This paper develops a novel measure of affordability that combines housing costs and transportation costs. It develops a measure of housing costs for owners and includes opportunity cost from commuting time in transportation costs. Households housing and transportation cost burdened increased from 1.2 to 1.9 million between 2007 and 2013 (58.6%). In São Paulo metropolitan region 27.7% of households spend over 45% of their income on housing and transportation by 2013. This broader measure of affordability points to integrating housing policy with infrastructure investments. Low cost housing located far from job center can result in a substantial number of cost burdened households.